Clientelist Policies in Late Liberalism: Mediterranean Europe - Barral Martínez, Margarita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2013)
In recent years, historiography has shown an increased interest in comparative analysis of socio-political states and evolutions—an excellent perspective from which to analyze modern history. The various manifestations of political clientelism appearing in Mediterranean Europe during the last quarter of the nineteenth century—caciquismo in Spain, opportunisme in France, and trasformismo in Italy—set the stage for political pragmatism, independent of ideological milieu, and also served as a bridge between the demise of liberalism and the emergence of democracies. These semi-official power relationships also represented attempts on the part of the elite and prominent individuals to bolster their position vis à vis the new movements and ideologies that brought about the society of the masses. In this article, we are attempting to reflect how the political clientelism that emerged in Mediterranean Europe during the transition from nineteenth to twentieth century: a) provided the stability required to initiate reforms in a socio-political milieu that was still taking shape and b) was a system that brought to light the contradictions between the legal context, founded on liberal principles, and how these principles were being applied by some of the elite who were striving to preserve a political and social order that was favorable to them.